Factor analysis of online repurchase intention on telemedicine services - Johan Hendri Prasetyo; Ch. Endah Winarti; Yohanes Ferry Cahaya; Markonah Markonah (Institute of Computer Science (IOCS), 2023)
Massive development that currently happen in digital world may affects various industrial sectors, including the health industry with its application of telemedice services. Through this phenomenon, this research has purpose to analyze the factors which could affecting online repurchase intention in one of the telemedicine services in Indonesia, namely Halodoc. The research method used is quantitative-causality through 200 respondents which taken by snowball method and then analyzed through PLS-SEM modeling. Research findings show the direct influence of e-service quality and e-recovery in increasing e-loyalty and online repurchase intention, moreover e-loyalty also found to have direct and indirect effect in boosting online repurchase intention.